Implementation of coherent Raman detected electron paramagnetic resonance - Gutschank, Jörg (Universität Dortmund, 2005)
The technique of coherent Raman (optically) detected electron paramagnetic resonance (ODEPR), is a relatively new method for the investigation of electronic structure. In this thesis the technique is implemented with a microwave frequency of 35 GHz for the first time. Two continuous wave (cw) ODEPR spectrometers have been built (14 and 35 GHz). Pulsed microwave excitation is possible at 14 GHz. The application to ruby demonstrates the working of the technique and the equipment. When ODEPR is used to analyse metalloproteins, conventional methods like electron paramagnetic resonance (EPR) and magnetic circular dichroism (MCD) are additionally needed. These have also been implemented and they are demonstrated on myoglobin (Mb).

The technique of coherent Raman (optically) detected electron paramagnetic resonance (ODEPR), is a relatively new method for the investigation of electronic structure. In this thesis the technique is implemented with a microwave frequency of 35 GHz for the first time.Two continuous wave (cw) ODEPR spectrometers have been built (14 and 35 GHz). Pulsed microwave excitation is possible at 14 GHz.The application to ruby demonstrates the working of the technique and the equipment.When ODEPR is used to analyse metalloproteins, conventional methods like electron paramagnetic resonance (EPR) and magnetic circular dichroism (MCD) are additionally needed. These have also been implemented and they are demonstrated on myoglobin (Mb).
Keywords: Elektronenspinresonanz; Kohärente Raman-Streuung; Electron spin resonance; ESR; Coherent Raman scattering; 530